Chemical, sensory and antioxidant characteristics of Bulgarian wines from native cultivars - Yoncheva, Tatyana (Array, 2019)
A study of the chemical composition, the antioxidant capacity and the sensory characteristics of three Bulgarian wines (vintage 2015) from the native cultivars Misket Vrachanski (white), Pamid (red) and Gamza (red), grown in the region of Pleven, Central Northern Bulgaria was carried out. The results showed that the wine composition was mainly determined by the cultivar and its peculiarities. Misket Vrachanski white wine had the lowest rate of sugar-free extract, glycerol, total phenolic compounds and the highest acid content. From the red wine samples, Pamid had lower rates for the above parameters compared to Gamza. The experimental wines were analyzed for total content of esters, aldehydes and higher alcohols. A correlation was found between the rates of the studied volatile components in the wines and their aromatic sensory characteristics. At the wine tasting, Misket Vrachanski that contained the most of esters and aldehydes, was the best evaluated, followed by Gamza and Pamid. There was no correlation between the amount of total phenolic compounds in the experimental samples and their antioxidant capacity, which according to ABTS and MRAP methods increased in the order of Pamid <Misket Vrachanski <Gamza.